Rate of Leptomeningeal Enhancement in Pediatric Myelin Oligodendrocyte Glycoprotein Antibody–Associated Encephalomyelitis. (October 2021) - Gadde, Judith A.; Wolf, David S.; Keller, Stephanie; Gombolay, Grace Y.
Introduction: Myelin oligodendrocyte glycoprotein antibodies (MOG-abs) are associated with demyelinating diseases. Leptomeningeal enhancement occurs in 6% of adult MOG-abs patients but rates in pediatric MOG-abs patients are unknown. Methods: Retrospective review of pediatric MOG-abs patients was performed. Results: Twenty-one patients (7 boys, 14 girls) were included with an average age of 8.6 years (range 2-15 years). Seven of 21 (33%) pediatric MOG-abs patients had leptomeningeal enhancement. Two patients' relapses were manifested by leptomeningeal enhancement alone and another patient presented with seizures, encephalopathy, and aseptic meningitis without demyelinating lesions. Cerebrospinal fluid pleocytosis was seen in both leptomeningeal (4/7 patients) and nonleptomeningeal enhancement (10/14 patients). Interestingly, 3 patients with leptomeningeal enhancement had normal cerebrospinal fluid white blood cell count. Cortical edema was more likely in patients with leptomeningeal enhancement ( P = .0263). Conclusion: We expand the clinical spectrum of anti-MOG antibody–associated disorder. Patients with recurrent leptomeningeal enhancement without demyelinating lesions should be tested for MOG antibodies.